The Influence Of Promotion And Quality Of Service On Purchasing Interest At Ibu's Prayer Gallery Fashion (Survey of Consumers at the Doa Ibu Ciawi Tasikmalaya Gallery Store) - Nurunnisa, Resa; Arisman, H Ari; Oktaviani, Nita Fauziah (Universitas Dehasen Bengkulu, 2024)
This research aims to determine the simultaneous and partial influence of promotion and service quality on purchase interest at the Doa Ibu Ciawi Tasikmalaya Gallery Store. The method used in this research is descriptive and quantitative methods. The population studied was 100 respondents. The data collected is in the form of primary data and secondary data. Data analysis in this research uses multiple regression analysis using SPSS 24 software. The research results show that promotion and service quality simultaneously have a significant effect on purchasing interest at the Doa Ibu Ciawi Tasikmalaya Gallery Store. Service quality partially has a significant effect on purchasing interest at the Doa Ibu Ciawi Tasikmalaya Gallery Store.